Knowledge Sharing: Bersama MGMP Bahasa Inggris SMK dalam Mengkonstruksi Soal Reading Comprehension Berorientasi HOTS - Imroatul Ma'fiyah; Ayu Istiana Sari (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Test construction and its implementation become an important aspect of assessment that need  to be understood for English teachers, especially in teaching reading comprehension. The activity of sharing knowledge with teachers in the Musyawarah Guru Mata Pelajaran (MGMP) community aimed at sharing experiences and knowledge on how to construct and apply assessments, especially on reading comprehension skills according to the characteristics of English subjects and the target skills to be achieved. The mechanism of knowledge sharing activities is carried out with several steps of assistance, including: determining the competencies to be measured, materials, formulating indicators, determining items, cognitive level and form of questions. As an evaluation and reflection step, it ends with a Focus Group Discussion (FGD). This activity has a positive impact on the quality of learning, this can be proven by the achievement of outcomes; implementation of HOTS-based test construction. It can also be seen the enthusiasm and motivation of teachers in following each stages of knowledge sharing